Validation of next-generation sequencing-based chimerism testing for accurate detection and monitoring of engraftment in hematopoietic stem cell transplantation - Kakodkar, Pramath; Zhao, Yayuan; Pan, Henry; Wu, Fang; Pearce, Twyla; Webster, Destinie; Elemary, Mohamed; Sabry, Waleed; Kwan, Luvinia; Pelzer, Lindsay; Bosch, Mark; Sherwood, Karen R.; et al. (Frontiers in Genetics, 2023)
Allogenic hematopoietic stem cell transplantation (allo-HSCT) is a life-saving treatment for various hematological disorders. Allo-HSCT's success depends on donor cells' engraftment and the elimination of recipient cells monitored through chimerism testing. Our aim was to validate an NGS-based chimerism assay for engraftment monitoring and to emphasize the importance of including the most prevalent cell subsets in the proficiency testing (PT) programs. We evaluated the analytical performance of the NGS-based chimerism (AlloSeq-HCT, CareDX) testing with a panel of targeted 202 informative single nucleotide polymorphisms (SNPs) (i.e., linearity and precision, analytical sensitivity and specificity, system accuracy, and reproducibility). We further compared the performance of our NGS panel with conventional short tandem repeat (STR) analysis in unfractionated whole blood and cell subset enriched CD3 and CD66. Our NGS-based chimerism monitoring assay has an impressive detection limit (0.3% host DNA) for minor alleles and analytical specificity (99.9%). Pearson's correlation between NGS and STR-based chimerism monitoring was a linear relationship with slope=0.8 and r= 0.973. The concordance of allo-HSCT patients using unfractionated whole blood, CD3, and CD66 was 0.95, 0.96, and 0.54, respectively. Utilization of CD3 + cell subsets for mixed chimerism detection yielded an average 7.3 ±7 fold higher donor percentage detection compared to its corresponding unfractionated whole blood samples. The accuracy of the NGS assay achieved a concordance of 98.6% on blinded external quality control STR samples. The reproducibility series showed near 100% concordance with respect to interassay, inter-tech, inter-instrument, cell flow kits, and AlloSeq-HCT software versions. Our study provided robust validation of NGS-based chimerism testing for accurate detection and monitoring of engraftment in allo-HSCT patients. By incorporating the cell subsets (CD3, and CD66), the sensitivity and accuracy of engraftment monitoring are significantly improved, making them an essential component of any PT program. Furthermore, the implementation of NGS-based chimerism testing has the potential to streamline high-volume transplant services and improve clinical outcomes by enabling earlier detection of relapse and guiding timely interventions.